Prospects of biological control of Phytophthora root rots of woody perennials with antagonistic fungi - Tsao, P.H. (Malaysian Plant Protection Society, 2013)
Although research activities on biological control of soilborne fungal diseases have increased dramatically in recent years, control of Phytophthora by antagonistic hyphomycetous fungi has remained largely unexplored. Our studies in recent years have shown that several species of Aspergillus, Penicillium, and Trichoderma, which exhibited in vitro antagonism, can be effective in suppressing Phytophthora root rot of azalea and sweet orange. In greenhouse pot experiments, under proper conditions, the severity of azalea root rot caused by Phytophthora cinnamomi or P.parasitica (=P.nicotianae) and citrus root rot caused by P.citrophthora or P.parasitica was reduced when Penicillium funiculosum grown in a bran/peat mixture was incorporated into a peat/perlite planting medium prior to Phytophthora inoculation. Aspergillus flavus, Trichoderma harzianum, and some other hyphomycetes were also effective in some tests. Several Aspergillus and Penicillium species also suppressed bark infection (gummosis) on stems of sweet orange or lemon by reducing the size of lesions caused by P.citrophthora or P. parasitica. These promising data have provided optimism for the prospects of effective biocontrol of Phytophthora root rot and crown rot of woody perennials in an integrated management sytem in the nursery